INTERNALISASI NILAI MODERASI BERAGAMA PADA ANAK USIA DINI MELALUI LINGKUNGAN BELAJAR PAUD YANG INKLUSIF - Lila Hikmawati; Nina Rohmatul Fauziyah; Masdar Hilmy; Abdul Muis Thabrany (LPPM IAD Probolinggo, 2026)
Religious and cultural diversity is an inherent social reality in Indonesia, requiring the early cultivation of tolerant and balanced religious attitudes. Early Childhood Education (ECE) plays a strategic role as the foundation for children’s character formation and social development, including the internalization of religious moderation values. This study aims to examine the process of internalizing these values among young children through an inclusive ECE learning environment. This research employs a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and the school principal, and documentation of instructional materials. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing. The findings reveal that the internalization of religious moderation values occurs through habituation in an inclusive learning environment, reflected in children’s empathy, tolerance, cooperation, and mutual respect in daily interactions. Teachers act as the primary agents by modeling appropriate attitudes and integrating moderation values into thematic, play-based learning. An inclusive environment is proven effective in fostering moderate attitudes in developmentally appropriate ways. This study highlights the importance of strengthening inclusive ECE settings and reflective-humanistic teacher roles to nurture moderate character from an early age.